The Silent Revolution the Arab Spring and the Gulf States - Seikaly, May; Mattar, Khawla (Gerlach Press, 2014)
How immune is the Gulf region to the changes that have engulfed the Arab world since 2011? This volume responds to this question by examining the impact of the Arab Spring on Gulf regimes and societies and contributing to debates on political participation and citizenship; sectarianism, gender and identity formation; as well as the role of the media in exposing the paradoxes of the Gulf system and its relationship to international political actors.